Further analysis of inhibitory effects of propranolol and local anaesthetics on the calcium current in Helix neurones. - Akaike, N. (Nature Publishing Group, 1982)
1 The effects of propranolol and local anaesthetics on Ca2+ current (Ica), individually separated from other ionic currents, in Helix neurones were studied under voltage clamp, using a suction pipette technique. 2 Increases in external Ca2+ concentrations overcame the inhibitory action of propranolol on Ica. Double reciprocal plots for peak Ica versus external Ca2+ concentrations in the presence or absence of propranolol did not intersect at the ordinate. 3 Internal application of propranolol (10-4M) inhibited Ica to about 40-60% of the control in a time-dependent manner. 4 Lignocaine and procaine at concentrations of 10-3-10-2 M inhibited Ica without shifting the threshold in the I-V relationships. Internal application of lignocaine (10-3-10-2M) also inhibited Ica: the ratio of depression of the Ica was almost equivalent to that of the agent applied externally. 5 The results provide evidence that propranolol inhibits Ica in the noncompetitive manner with Ca2+ at the cell membrane, and suggest that the agents may occupy the receptor site in the Ca2+-channel somewhere between the outer surface and inner phase of the membrane.